Methodology for assessing the agroecological adaptability of genotypes under global climate warming - A. I. Kincharov; E. A. Demina; M. N. Kincharova; T. Yu. Taranova; O. S. Mullayanova; K. Yu. Chekmasova (Труды по прикладной ботанике, генетике и селекции)
Background. The relevance of the research is due to the fact that, despite the breeding achievements in releasing cultivars with high potential yield and resistance to the most common stressors in the regions, it is almost impossible to foresee and accurately predict the reaction of cultivars under production conditions. Besides, extreme weather events, including heat waves, droughts and downpours, will increasingly manifest themselves under global climate warming. To reduce the risk of a significant decrease in gross grain harvests in dry years and achieve high results under favorable conditions, the goal was to develop a comprehensive indicator for assessing the agroecological adaptability of genotypes to some consequences of global climate warming.Materials and methods. The results of a competitive test of 5 cultivars and 9 promising lines of spring wheat for their yield across six years contrasting in moisture availability by calculating the indicators of responsiveness to favorable conditions, grain yield depression under unfavorable conditions and the relative yield index were used to develop a complex indicator proposed to assess the agroecological adaptability of a genotype to contrasting environmental conditions.Results. The proposed method makes it possible to perform a comprehensive assessment that takes into account the responsiveness of an accession to improved agroclimatic conditions and the degree of its reaction to adverse environmental factors, taking into account the yield index in the studied set. The method is recommended for evaluating the source material and identifying the diversity of its responses to changes in agroclimatic conditions as well as for the stage of competitive variety testing in plant breeding for adaptability.